Enhancing Mineral Content in Cookies: Beetroot and Holy Basil Composite Flour with Butter and Margarine - Lucia Crysanthy Soedirga; Alvin B. Ilianto (University of Sultan Ageng Tirtayasa, 2025)
Cookies are a popular snack with many varieties available on the market. While the use of beetroot in cookies is relatively common, incorporating holy basil is rare, with limited research on its potential. This study explores composite flour made from beetroot and holy basil as a substitute for wheat flour, aiming to enhance the mineral content in cookies. The objective is to identify the preferred ratio of beetroot to holy basil flour (100:0, 90:10, 80:20, 70:30, 60:40) and the type of fat (butter or margarine) for improved mineral content, fat content, hardness, and spread ratio. The best formulation was an 80:20 ratio of beetroot to holy basil flour combined with butter. This formulation contained 160.01±3.17 mg/100g of calcium, 5.85±0.24 mg/100g of iron, and 46.62±0.04 mg/100g of magnesium. Additionally, it had a fat content of 23.43±0.46%, a hardness of 2047.06±35.06 g, and a spread ratio of 6.17±0.41.